Payments for environmental services to strengthen ecosystem connectivity in an agricultural landscape. (3rd August 2018) - Bateman, Laura; Yi, Dale; Cacho, Oscar J; Stringer, Randy
Abstract: This article investigates the use of payments for environmental services to support a wildlife corridor between two Priority Tiger Conservation Landscapes in central Sumatra, Indonesia. Several hundred smallholders operate within a Protection Forest linking the Tiger Conservation Landscapes. This study explores the willingness of these smallholders to accept a payment requiring them to forgo access to their land for five years. In addition to asking households directly what they would be willing to accept (WTA), we also ask them to infer what their neighbour would accept. The study finds evidence of hypothetical bias in the conventional WTA values, with a statistically significant difference between what people say they would be willing to accept when surveyed, compared to what they say would actually be willing to accept in a 'real life' situation. We show how inferred valuation techniques can mitigate against this.